2017
DOI: 10.4103/jrpp.jrpp_16_151
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pharmacist intervention on appropriate insulin pen use in older patients with type 2 diabetes mellitus in a rural area in Iran

Abstract: Objective:The aim of this study was to evaluate the impact of pharmacist-conducted educational intervention on reducing errors related to inappropriate insulin pen use.Methods:This was a prospective, before-after study with an educational intervention component. The study was conducted on 122 elderly diabetic patients. Data were collected through interviews using researcher-administered questionnaires as well as patients’ medical records. Patients were asked about the preparation, injection, and storage techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 22 publications
0
13
0
4
Order By: Relevance
“…Majority of patients who have been advised on proper disposal got this information from their nurse or physician, and only 9% of them received such instruction from pharmacists. One study in Iran found that pharmacists can play an important role in safe and efficient use of insulin pen in elderly diabetic patients including its proper disposal as well ( 16 ). Pilot study conducted in Guyana found that, with training, nurses and pharmacists were able to counsel clients successfully resulting in insulin needle re-use declined from 87% to 8% with the provision of full supply and clients felt safer using a single needle for each injection, disposing used syringes into containers and returning full containers to facilities for disposal ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Majority of patients who have been advised on proper disposal got this information from their nurse or physician, and only 9% of them received such instruction from pharmacists. One study in Iran found that pharmacists can play an important role in safe and efficient use of insulin pen in elderly diabetic patients including its proper disposal as well ( 16 ). Pilot study conducted in Guyana found that, with training, nurses and pharmacists were able to counsel clients successfully resulting in insulin needle re-use declined from 87% to 8% with the provision of full supply and clients felt safer using a single needle for each injection, disposing used syringes into containers and returning full containers to facilities for disposal ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare professionals should educate and reinforce patients and their relatives about the correct use of insulin pens during their first visit and subsequent follow-ups. They can play a significant role in safe and efficient use of insulin pens in diabetic patients [ 31 ]. Our study had few limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Educational interventions with pharmacists also has an important role in ensuring appropriate insulin practices. [32] As seen in our study, certain practices such as use of re-suspension technique and systemic site rotation was practiced by only 50% of the nurses in the first observation period. Even though, there was a significant increase in these were practices, the proportion remained lower compared with other practices.…”
Section: Discussionmentioning
confidence: 50%